2015
DOI: 10.20286/ijtmgh-0303131
|View full text |Cite
|
Sign up to set email alerts
|

Trend of the Esophageal Cancer Incidence in IRAN

Abstract: Introduction: Cancer is one of the main causes for mortality and morbidity in the world. Identifying epidemiology and the trend of esophageal cancer may be highly effective in related planning. The present study has been carried out with the aim of exploring the morbidity and trend of esophageal cancer in Iran. Methods:The present study is a type of repeated analysis of the existing data. The population of this study consisted of the cancer registry data during the years (2003)(2004)(2005)(2006)(2007)(2008)(20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Colorectal cancer (colon and rectum) is a common disease with different incidence in different areas of the world and is considered as a health problem in communities (Ansari et al, 2007;Khazaei et al, 2015). Despite of remarkable advances in medical sciences, cancer is an important disease and the second cause of death after cardiovascular diseases (Farzianpour et al, 2014;Jafari et al, 2015;Khazaei et al, 2016;Moradi et al, 2016). The results of different genetic, experimental, and epidemiological studies indicated that colorectal cancer develops as a result of mutual effects of genetic talent, environmental factors, and lifestyle (Ansari et al, 2007;Shadmani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (colon and rectum) is a common disease with different incidence in different areas of the world and is considered as a health problem in communities (Ansari et al, 2007;Khazaei et al, 2015). Despite of remarkable advances in medical sciences, cancer is an important disease and the second cause of death after cardiovascular diseases (Farzianpour et al, 2014;Jafari et al, 2015;Khazaei et al, 2016;Moradi et al, 2016). The results of different genetic, experimental, and epidemiological studies indicated that colorectal cancer develops as a result of mutual effects of genetic talent, environmental factors, and lifestyle (Ansari et al, 2007;Shadmani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Ministry of Health, the level of records has increased from 18% in 1999 to 80% in 2005 (54), which may indicate the high level of cancers, and especially lung cancer, in Iran. Therefore, it is necessary to pay attention to the evolving trend of the cancer records system as had been mentioned in other cancer studies in Iran (55)(56)(57)(58)(59)(60). Though how much of the increase and what geographic areas are related to this issue should be investigated in future studies which normally is common in many countries by and large.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, the incidence of many cancers, especially CRC, varies depending on the geographical situation of the area and has its own spatial pattern (20)(21)(22)(23)(24). Usually, Poisson regression is employed as the model for studying the correlation between variables at the level of a geographical unit with an outcome that is count.…”
Section: Introductionmentioning
confidence: 99%